2017
DOI: 10.1111/ajd.12668
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of lymphangioma circumscriptum: A morphological study of 45 cases

Abstract: Dermoscopy is useful in improving the diagnosis of lymphangioma circumscriptum with characteristic structures and patterns and could assist in elucidating the presence of blood in lymphatic channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 13 publications
5
56
0
4
Order By: Relevance
“…Cutaneous lymphangiomas (CL) are uncommon cutaneous lesions, accounting for 4% of all vascular tumors . CL are usually congenital, although they may appear spontaneously in adolescence or adult life, showing a slight female prevalence, as reported also in our case.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Cutaneous lymphangiomas (CL) are uncommon cutaneous lesions, accounting for 4% of all vascular tumors . CL are usually congenital, although they may appear spontaneously in adolescence or adult life, showing a slight female prevalence, as reported also in our case.…”
supporting
confidence: 82%
“…However the authors called these lesions CLC and did not use the new classification of MCLM . Besides, among the 45 cases reported by the authors in their study, only one case showed clinical and dermoscopic features similar to our case.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…The white scar like patch is a sharply demarcated but irregularly defined white area. It histologically correlates to fibrosis in the papillary dermis [9]. Comedo like openings and milia like cysts are the classical diagnostic criteria for seborrheic keratosis on dermoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor , A 70‐year‐old man presented with a 3‐week history of multiple papules, which were vascular in appearance, on his trunk (a); 10 years previously he had undergone complete excision of a superficial spreading malignant melanoma from his abdomen. (b) On polarized light dermoscopy, the papules showed an angioma‐like pattern, with translucent‐to‐pink pseudolagoons, white lines and a hypopyon sign reminiscent of that classically described in lymphangioma (arrow) . Polymorphous atypical vessels inside the pseudolagoons were also observed (arrowhead).…”
mentioning
confidence: 81%